1984
DOI: 10.1161/01.cir.69.1.87
|View full text |Cite
|
Sign up to set email alerts
|

Significance of ventricular arrhythmias initiated by programmed ventricular stimulation: the importance of the type of ventricular arrhythmia induced and the number of premature stimuli required.

Abstract: An increasing number of premature ventricular stimuli are being used during programmed stimulation of the heart in the investigation of patients with documented or suspected ventricular arrhythmias. To analyze the significance of the different types of ventricular arrhythmias that are initiated, we evaluated in a prospective study the effect of from one to four ventricular premature stimuli in 52 patients without (non-VT group) and 50 patients with (prior-VT group) documented ventricular tachycardia or ventric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0

Year Published

1986
1986
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 301 publications
(55 citation statements)
references
References 26 publications
(2 reference statements)
0
55
0
Order By: Relevance
“…35 Multiple premature stimuli appear more effective than a single premature stimulus. 36 Our results suggest that the use of different drive and premature sites may be effective in initiating a reentrant rhythm. Recently, Frazier and coworkers37 showed that colliding wave fronts derived from perpendicular drive and premature stimulus sites could initiate a reentrant rhythm.…”
Section: Discussionmentioning
confidence: 71%
“…35 Multiple premature stimuli appear more effective than a single premature stimulus. 36 Our results suggest that the use of different drive and premature sites may be effective in initiating a reentrant rhythm. Recently, Frazier and coworkers37 showed that colliding wave fronts derived from perpendicular drive and premature stimulus sites could initiate a reentrant rhythm.…”
Section: Discussionmentioning
confidence: 71%
“…28 Moreover, during programmed stimulation, the likelihood of inducing reentry increased as the number of extrastimuli increased. 29,30 It is possible that a premature stimulus preconditioned the electrophysiological substrate and, accordingly, altered the likelihood of inducing reentry by a second (S 3 ) and possibly a third (S 4 ) premature stimulus. The results of the present study also suggested that in some circumstances, suitable conditions for reentry may not exist during baseline pacing but can form dynamically during premature stimulation of the heart.…”
Section: Discussionmentioning
confidence: 99%
“…The use of a more rigorous and standarized stimulation protocol (double and triple extrastimulation) in all patients in the future would both increase the number of patients in whom ventricular tachycardia could be induced, and allow postulations regarding the mechanism. [55][56][57][58] Treatment. Once the decision to treat was made, a drug effective in preventing or controlling ventricular tachycardia could be identified in 14 of 17 patients (82%) with a combined approach of programmed stimulation, treadmill testing, and Holter monitoring.…”
Section: Discussionmentioning
confidence: 99%